Diversion Process as a Transformative Reform of the Criminal Justice System for Children in Conflict with the Law - Yoga Ristama; Hibnu Nugroho (Magister of Law, Faculty of Law, University of Mataram, 2026)
This article examines the important of applying restorative justice principles in Indonesia’s juvenile justice system. The principle of child protection emphasises processes that are free from violence on safeguarding children’s rights, welfare, development, and overall well-being, including cases involving children in criminal acts. However, the current implementations of diversion and restorative justice often remains limited in its ability to address the underlying systemic and structural issues that lead to juvenile delinquency. These limitations underscore the need for a shift toward transformative justice, which seeks not merely to resolve individual conflicts, but also to confront and remedy their underlying causes. In this context, this article adopts a conceptual approach grounded in doctrinal legal research. The analysis employs systematic and teleological of interpretation to examine the legal norms within the juvenile justice framework. This research uses a normative juridical research design, with data collected through a literature review and analysed qualitatively. The findings of the study show that transformative justice in handling children’s cases in Indonesia calls for legal reform through the expansion of the restorative justice approach under the SPPA Law. Transformative justice offers an alternative framework that move beyond a narrow focus on legal sanctions by also considering the child’s personal circumstances, including social background and family conditions. As such, this concept supports a more holistic approach to child development and provides a more comprehensive framework for handling cases involving children.